Mastering modern world history - Lowe, Norman; Traynor, John (New York : Bloomsbury Academic, 2022)
"The sixth edition of this bestselling book takes students on a journey through the 20th century and provides a clear overview of the key events which have shaped modern world history. Unrivalled in its broad coverage, it: Surveys international relations and war, from 1900 to the present day--Examines the rise and fall of fascism and communism around the globe--Explores the international affairs of the major superpowers: the USA, Russia/USSR and China--Assesses the experience of decolonization in India, Africa and Latin America--Unpicks global issues, including economic crises and population increase Chapters feature maps, diagrams and further reading suggestions to support and further understanding. This new edition has been updated to take account of new scholarship, and provide a more global approach to key chapters in modern world history"--
The Origins of the First World War -- The Great War 1914-1918 -- A Bitter Peace 1918-33 -- The Road to War -- The Second World War, 1939-45 -- The Cold War : problems of international relations after the Second World War -- The spread of communism outside Europe and its effects on international relations -- The United Nations Organization -- The Two Europes, East and West since 1945 -- Conflict in the Middle East -- The New World Order and the War Against Global Terrorism -- Italy 1918-1945 : the first appearance of fascism -- Germany 1918-1945 : the Weimar Republic and Hitler -- Russia 1894-1917 -- Russia under Lenin and Stalin -- Continuing communism, collapse and aftermath, 1953 to the present -- China 1900-49 -- China since 1949 : the communists in control -- Communism in Korea and South East Asia -- USA Boom and Bust: 1900-29 -- Roosevelt and the New Deal : 1929-45 -- USA 1945-68 : Uneven Prosperity -- USA 1968-2012 : Opportunity and Challenge -- The end of the European Empires -- Africa since independence -- Latin America -- The changing world economy since 1900 -- The World's Population.
Includes bibliographical references and index.
Keywords: History, Modern -- 20th century; History, Modern -- 21st century